Enhancing clinical research with alcohol, tobacco and cannabis problems and dependence - Allsop, Steve; Carter, Owen; Lenton, Simon (Informa Healthcare, 2010)
A strong body of evidence guides clinical responses to alcohol and tobacco dependence and there is an emerging evidence base informing responses to cannabis dependence. Nevertheless, there are still important gaps in the evidence base. Approach. Three researchers, with backgrounds in alcohol, tobacco and cannabis research examine current clinical research and practice to identify potential future priorities for clinical research. Key Findings. Clinical outcomes will be improved by research that enhances engagement and retention of a broader range of consumers, especially underrepresented and disadvantaged populations who may not respond as well to mainstream interventions. Research might focus on innovative client recruitment approaches, varying treatment intensity, use of new technology and assertive outreach. Assessment of treatment outcome will be enhanced by strategies that facilitate longer-term follow up of participants, adoption of shared measures of non-abstinent outcomes and extending the focus and outcome measures beyond drug use.Translation of research into clinical strategies will be enhanced by improving links between theory and interventions, increased attention on factors that influence treatment fidelity, designing treatment studies that are relevant to a variety of clinical settings, focussing on clinician characteristics as treatment variables and developing methodologies that address the capacity of participants to discriminate between placebo and pharmacotherapy. Implications. A range of future research priorities have been identified that have the potential to better engage and retain clients in a range of treatment settings and enhance translation of research findings into improved treatment outcomes.